A sociological approach to the business-ification of the health sector in Chile - Manzano Méndez, Daniel (Revista Chilena de Salud Pública, 2020)
This work aims to perform a sociological analysis of health entrepreneurship in to¬day’s Chile from the perspective of Bourdieu’s field theory. We carry out a structural review of the health model in Chile and then reflect on the delegated power of the business actor from the Goldthorpe and Wright class structure. Finally, based on the characteristics of this actor, it is proposed to research his role in the public sphere in a context of deepening the divorce between politics and society.